COMPARATIVE EFFECT OF GUIDED-DISCOVERY METHOD ON CACHIEVEMENT IN FINANCIAL ACCOUNTING AMONG SECONDARY SCHOOL STUDENTS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This research investigated the effect of the conventional method of teaching and theguided-discovery method of teaching on students' achievement in financial accounting insenior secondary schools in Anambra State. Three research questions and three hypothesesguided the study. The quasi-experimental research design was utilized for the study. Thepopulation comprised all the ninety SS 2 financial accounting students in Awka and AguataEducation zones of Anambra state. The Financial Accounting Achievement Test (FAAT) wasused for data collection. Mean, standard deviation and analysis of co-variance (ANCOVA)were used for data analysis. Findings indicated that students taught with guided-discoverymethod scored higher than those taught with conventional teaching method. The study alsorevealed no significant difference in the mean performance scores of male and female students taught with guided-discovery and conventional methods of teaching respectively. The study concluded that teacher's predominant usage of conventional method of instruction in teaching Financial Accounting is a contributory cause of students' failure in the subject and the use of guided-discovery method in place of conventional method will improve students' achievement in the subject. Consequently, it was recommended among others that government at all levels should improve the education sector through training of teachers in the use of effective instructional methods in the classroom, especially in the use of guided-discovery method in Financial Accounting instruction and possibly other school subjects